Implementasi Metode MAUT dalam Sistem Pendukung Keputusan Penentuan Bibit Udang Vaname Unggul - Mustafa Kamal; Iskandar Zulkarnaini; Sriwinar (Jurnal Ilmu Komputer Aceh, 2026)
The success of whiteleg shrimp cultivation depends heavily on the selection of high-quality seeds. However, the seed selection process in the field is often subjective and based solely on intuition. This study aims to design and implement a Decision Support System (DSS) using the Multi-Attribute Utility Theory (MAUT) method to help farmers objectively determine superior whiteleg shrimp seeds. The MAUT method was chosen because of its ability to convert the values of various criteria into a uniform utility scale that can be compared mathematically. The criteria used in the assessment include body color, active movement, body shape, full intestines, fluffy tail, and bright eyes. The results showed that the developed system can provide the best seed recommendations based on the highest preference value. Based on testing, the SPF Global Gen Vannamei Shrimp Seed alternative obtained the highest score (1.0000) and became the main recommendation in seed selection.